Acculturation of Religion and Culture Within Muslim Sundanese Society in West Java - Yanti, Fitri; Witro, Doli; Putra, D.I. Ansusa; Ilahi, Restu Prana; Intania, Naila; Alghani, Raid (Al-Albab, 2024)
This article explores the acculturation of culture and religion, focusing on the interaction between Islam and Sundanese culture in West Java, Indonesia. Early Islamic preachers employed accommodating strategies, integrating pre-existing cultural elements, which led to the development of a unique form of Islam in the region. The purpose of this article is to examine and highlight the ways in which Islam has blended with Sundanese culture in West Java. The study utilized a qualitative research approach, combining field research with data from both primary sources (observations and interviews) and secondary sources, such as books, scholarly articles, research reports, and other relevant materials. The data were displayed in a narrative-descriptive format and analyzed using the qualitative data analysis techniques including data condensation, data display, and conclusion drawing. The findings reveal that the long-standing process of acculturation between Islam and Sundanese culture in West Java has produced a distinct Sundanese culture influenced by Islamic principles. This is evident in elements such as the wawacan texts, which contain Islamic teachings, the prevalence of Islamic boarding schools, the practice of Islamic mysticism (Sufism-Tariqa), and the unique Islamic-Sundanese architectural style. The widespread acceptance of Islamic teachings among the Sundanese has led to the incorporation of these principles and traditions into Sundanese society, aligning them closely with Islamic values.